AB252. The positive expression of SET8 possesses prognostic relevance and mediates Wnt target gene activation in renal cell carcinoma - Shen, Tianyi (Transl Androl Urol, 2016)
BACKGROUND: Renal cell carcinoma (RCC) is common renal malignancy within poor prognosis. Histone methylase SET8 plays vital roles in tumorigenesis through regulating Wnt/β-catenin signaling and other cancer-related pathways. Here, we studied the expression and function of SET8 inccRCC METHODS: Our study was performed immunohistochemistry to assess the overall levels of SET8 and β-catenin in a tissue microarray with 50 RCC specimens. Then, we examined the protein levels of SET8 in RCC and reduced the expression of SET8 by shRNA-mediated partial depletion in order to systematically investigate whether SET8 was involved inRCC carcinogenesis and tumor development measured by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) assay, trans well assay and flow cytometry, respectively. Protein and mRNA expression were assayed by western blotting and quantitative real-time PCR (qPCR). The association between proteins was assayed by co-immunoprecipitation. RESULTS: SET8 levels and the abnormal expression of β-catenin in the diverse RCC subtypes were inversely correlated with Fuhrman grading, pT stage, and metastasis. Further, shRNA-mediated partial depletion of SET8 reduced 786-0 and ACHN cell viability, arrested them at S phase of the cell cycle and inhibited their abilities of invasion and metastasis. Moreover, western blot implied that several protein expressions of Wnt target genes were inhibited by SET8 interference. It was found that SET8 directly interacted with lymphoid enhancing factor-1 (LEF1)/TCF4, and regulated the transcription of Wnt-activated genes, possibly through H4K20monomethylation at the target gene promoters. CONCLUSIONS: Collectively, these results suggested that SET8 could serve as a promising biomarker and contribute to predicting distal metastasis and prognosis of patient with RCC.